Pengaruh Self Efficacy Dan Dukungan Sosial Terhadap Motivasi Berprestasi Atlet Rugby UNUGIRI - Da'i, Mohamad; Cahyaningrum, Vesti Dwi (Universitas Nusantara PGRI Kediri, 2023)
This research was conducted to determine the influence of self-efficacy and social support on the achievement motivation of Rugby athletes. The research sample consisted of 50 Rugby athletes from the UNUGIRI Student Activity Unit. The author created the measurement instrument by referring to the components of achievement motivation by McClelland, measuring self-efficacy using the Physical Self-Efficacy Scale (PSE) by Rycman, and referring to the aspects of social support described by Sarafino. The results of the study showed that there is a significant influence of self-efficacy, social support, and demographic variables (gender and age) on the achievement motivation of UNUGIRI Rugby athletes. For further research, researchers can design studies using other research methods or using other relevant variables. For athlete managers, this study can be used as a reference to improve the achievement motivation of athletes by optimizing self-efficacy and social support.